Parametric optimization of flow in a solar chimney power plant under variable semi elliptical constraints - Rajamurugu Natarajan; S. Yaknesh; K B Prakash; Mohammed Al Awadh; Qasem M. Al-Mdallal (Scientific Reports)
Abstract In response to the ongoing quest for more efficient renewable energy sources, this research addresses a significant gap in understanding the performance variations of Solar Chimney Power Plant (SCPP) models, particularly focusing on the influence of flow parameters in full and half-inclined collector sections featuring semi-elliptical curvature. The motivation stems from the need to optimize SCPP designs for enhanced energy generation while minimizing resource utilization and environmental impact. This research focuses on investigating flow parameter variations in Solar Chimney Power Plant (SCPP) models with full and half-inclined collector sections featuring semi-elliptical curvature and variable semi-minor heights (b: 0.01–0.03 m). The six models, including divergent chimneys (4 m), collector diameter (2.6 m), and 0.04 m collector inlet height at a 10° positive inclination, were categorized into Full Inclined Semi Elliptical Solar Chimney Power Plants (FSCPP-1,2,3) and Half Inclined Semi Elliptical Solar Chimney Power Plant (HSCPP-1,2,3). Initially, ANSYS-FLUENT were utilized for computational approximation. The models with greater maximum flow parameter magnitudes were selected for experimentation. FSCPP-1 and HSCPP-1 demonstrated superior performance, achieving higher maximum velocities (4.31 m/s, 4.49 m/s) under a temperature rise of 35 K and 36 K. Experimental results aligned well with computational data. Validation with a straight tower inclined collector solar chimney (SSCPP) and existing literatures concluded that the semi-elliptical profile in the half-inclined collector model (HSCPP-1) enhances overall system performance. In addition, a comparison between computational and experimental approaches revealed an error approximation of up to 5%. FSCPP-1 outperformed its subgroup with velocity and temperature enhancements up to 5% and 2%, while HSCPP-1 surpassed its group with 4% and 1% enhancement. Validation with SSCPP highlighted the maximum velocity enhancements of up to 42% in FSCPP and 44% in HSCPP models. In higher flow parameter magnitude models, HSCPP-1 outperformed FSCPP-1 with a 4% enhancement in maximum velocity and up to 2% in temperature magnitude, emphasizing the positive influence of curvature heights (0.01–0.03 m) progressing towards minimal positive percentage enhancements.